PERAN GURU DALAM PEMBENTUKAN KARAKTER SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DIKELAS VIII MTS AL-MA’ARIF 02 SINGOSARI - Peny Wahyuni; Azhar Haq; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Character building is the main thing that needs to be done in improving the quality of society and students in particular. The formation of character must be in line with the formation of our piety to Allah SWT. Although various efforts have been made to shape the character of the community and students in particular, it has not been carried out optimally and their influence on the formation of good behavior has been carried out. As an educator, especially a teacher of Akidah Akhlak, you should pay attention to forming good behavior. Good behavior in students shows the success of teacher guidance to students, because good behavior is very important to find a student's identity as a provision in the future and when he is already living in the community. This study uses a phenomology-based qualitative approach with the type of case study research, the results of this study indicate that the teacher's role in character building is done for the better. This is supported by concrete or clear supporting factors carried out by the teacher, namely the teacher's ability to master the subject matter of Akidah Akhlak, facilities in the form of learning media, supporting books, and adequate classroom facilities to help shape student character. The obstacle faced by Akidah Akhlak teachers is that there are still many students who do not obey the rules made by the principal and class teachers.